Validation of a simplified Chinese version of the 3 × 2 Achievement Goal Questionnaire (AGQ-S). Issue 1 (2nd January 2022) - Zhou, Mingming; Teo, Timothy; Hoi, Cathy Ka Weng
Abstract: This paper reports on the development of a shortened version of the 3 × 2 achievement goal questionnaire, a psychometrically sound, theoretically driven, self-report measure. The shortened version (AGQ–S) which contains 12 items and six subscales improves on the original version in three ways: It eliminates the redundant frequency scale, simplifies the scoring of the subscales, and reduces overlap across subscales. The reliability and validity of the AGQ–S were examined within 177 undergraduates from mainland China (46.3% females, mean age = 20.53; SD = 1.31); 158 undergraduates from Macau (61.9% females; mean age = 20.64; SD = 1.67), and 348 5th-graders from mainland China (54.0% females; mean age = 11.56; SD = 0.59), respectively. Confirmatory factor analyses showed acceptable fits of the data for the 12-item model in both studies ( χ 2 /df ranged from 1.24 to 1.70; CFI, IFI, and TLI were all above 0.97). Thus, the scores of the Chinese version of the AGQ–S were found to be valid and reliable. The short form was deemed sufficient for psychological research contexts with extremely limited time constraints.